Study on the adsorption process of monoethanolamine (MEA) wastewater using untreated rice husk and treated rice husk - Zulhafiz, Zulkifli (2013)
Monoethanolamine (MEA) is commonly used for treating synthesis gases stream formed in ammonia, hydrogen, carbon monoxide, and flue gas facilities. Throughout shutdown and maintenance of these facilities, high concentrations of residual alkanolamine may be carried over into the wastewater, as a result of which they can disturb the biological treatment system of the plant. This research was conducted to determine the best adsorbent and process condition in treating MEA wastewater via adsorption method by observing three parameters that are residue oil, COD and at the same time to maintaining the amine concentration level. There were two differents type of adsorbents were used which are untreated rice husk and treated rice husk. The batch adsorption process were used to determine the best adsorbent. The parameters were used in this experiment was the adsorbent dosage, and mixing speed. From the result that collected, treated rice husk has potential as an adsorbent to in removing residue oil with up to 51%, reducing COD up to 66% compared to untreated rice husk which reduce oil up to 47%, and COD up to 54% while the amine concentration were remained same after the treatment for both adsorbents.